2018
DOI: 10.1016/j.ijsu.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs laparoscopic splenectomy for splenomegaly: A retrospective comparative cohort study

Abstract: Robotic splenectomy for splenomegaly is associated with less blood loss and longer operative times than the laparoscopic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
4
19
0
Order By: Relevance
“…The operative time was longer in the robotic group in the ROLARR trial, but this could be attributed to the status of the learning curve in robotic rectal surgery of the participating surgeons. As robotic procedures have always been associated with longer operative times as compared to laparoscopy in several general surgery procedures, 2–5 , 18 , 19 we believe that this result for rectal surgery further supports the hypothesis that the use of the robotic platform may be particularly indicated for rectal cancer surgery.…”
Section: Discussionsupporting
confidence: 67%
“…The operative time was longer in the robotic group in the ROLARR trial, but this could be attributed to the status of the learning curve in robotic rectal surgery of the participating surgeons. As robotic procedures have always been associated with longer operative times as compared to laparoscopy in several general surgery procedures, 2–5 , 18 , 19 we believe that this result for rectal surgery further supports the hypothesis that the use of the robotic platform may be particularly indicated for rectal cancer surgery.…”
Section: Discussionsupporting
confidence: 67%
“…Currently, with the advanced minimally invasive method, robotic splenectomy has been used for first training of robotic systems and routine clinical practice. Cavaliere et al suggest robotic splenectomy due to less intraoperative bleeding for splenomegaly (26). On the other hand, Bodner et al and Gelmini et al have reported that robotic surgery is not cost-effective and the operation time is longer than in LS (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of this technology is greater than the classic laparoscopy and the results have been better, especially when using a single port with less inflammatory organic response to the surgical trauma. In a few years, the robotic approaches will be the standard option for most surgeries of all specialities, even in elderly patients [1,2,21].…”
Section: Opsoninsmentioning
confidence: 99%
“…In such cases, a subtotal splenectomy is recommended to alleviate the symptoms and to improve the results of chemotherapy, without reducing the patient's immune defences, followed by severe sepsis and precocious death due to an asplenic condition if a total splenectomy needs to be performed. The advances of imaging methods and imaging guided biopsies have been enough to define the stage of oncological diseases, including Hodgkin's and non-Hodgkin's lymphomas; therefore, surgical procedures must be avoided [21,26,27,28,29] .…”
Section: Splenic Diseases In the Elderlymentioning
confidence: 99%